The wicked + the divine. Vol. 9, "OKAY" - Gillen, Kieron (Image Comics, 2019)
"FINAL STORY ARC! After five years, we reach the final volume. We do not go gentle into that good night, but go driving a converted tank, covered in glitter and spangles, with a sound system audible from Mars blaring nothing but bangers. Gods, pop stars, an ending. We'll miss you"--Provided by publisher.